Efeitos do alprazolam no desenvolvimento do Sistema Nervoso Sensorial e Motor da prole - Mascarenhas, Fernanda Naves Araújo do Prado (2020)
The use of benzodiazepines (BZDs) during pregnancy, especially alprazolam, is common and its impact on the fetal neural tissue is not known. In this sense, the present study aimed to investigate the effects of alprazolam on the Central Nervous System (CNS) of Wistar rat pups exposed to the drug. Thirty animals (24 females and 6 males, CEUA protocol 014/17) were used. Females were divided into three groups (n = 8): control (TC, 0 mg / animal), treatment 1 (T1, 1.25 mg / animal) and treatment 2 (T2, 30 mg / animal). With two males per group for copulation. Alprazolam was administered orally ten days before copulation and throughout pregnancy. We evaluated: the number of individuals per litter, the percentage of males and females per litter, the weight of mothers and pups, the macroscopic changes of the brain. And, in the pups' olfactory bulb and cerebellum, we evaluated: cell density and size, gliosis, synaptic density, inflammation, and oxidative stress. The results showed no significant differences regarding the number and sex of pups, body weight of mothers and pups, and macroscopic changes of the brain. Regarding morphology, the two areas analyzed showed no differences in cell density, but in the cerebellum a significant decrease in the amount of smaller cells was detected in T1 and T2 groups. Of all proteins analyzed by Western blotting, the cerebellum showed increased expression of Iba-1 and NF-κBp65 in T1 group compared to the other groups. The olfactory bulb, on the other hand, showed no alterations in the protein expressions. Oxidative stress experiments showed an increase in oxidative degradation of lipids in groups T2 compared to T1 in both regions and increased levels of carbonyl proteins in group T1 compared to CT in the cerebellum. We conclude that treatment with alprazolam during pregnancy may be involved with cellular changes that most affected the pups' cerebellum.